2017
DOI: 10.1175/jcli-d-16-0852.1
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variability of Sea Surface Temperature in the Southwest Pacific and the Role of Ocean Dynamics

Abstract: This paper investigates the mechanisms causing interannual variability of upper ocean heat content and sea surface temperature (SST) in the southwest Pacific. Using the ECCOv4 ocean reanalysis it is shown that air–sea heat flux and ocean heat transport convergence due to ocean dynamics both contribute to the variability of upper ocean temperatures around New Zealand. The ocean dynamics responsible for the ocean heat transport convergence are investigated. It is shown that SSTs are significantly correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 39 publications
5
38
0
Order By: Relevance
“…Here we present a novel application of this approach to a recent observational estimate of OHT over the 1992-2011 period. This gridded OHT estimate is part of a global ocean state estimate that agrees, within expected uncertainty ranges, with the bulk of available ocean observations collected between 1992 and 2011, including millions of Argo profiles and complementary satellite data, as well as with atmospheric re-analysis estimates (17)(18)(19)(20)(21)(22)(23)(24).…”
supporting
confidence: 67%
“…Here we present a novel application of this approach to a recent observational estimate of OHT over the 1992-2011 period. This gridded OHT estimate is part of a global ocean state estimate that agrees, within expected uncertainty ranges, with the bulk of available ocean observations collected between 1992 and 2011, including millions of Argo profiles and complementary satellite data, as well as with atmospheric re-analysis estimates (17)(18)(19)(20)(21)(22)(23)(24).…”
supporting
confidence: 67%
“…It is evident that a complete understanding of climate variability and change will require an ability to robustly assess changes like those observed over the past two decades in the Indo‐Pacific region. Using the ECCO model output (Bowen et al, ; Buckley et al, ; Thompson et al, ), we found that the ITF plays a major role in climate variations of global consequence. The ITF, however, may experience a substantial decrease in the future based on climate models and ocean downscaling models (Feng et al, ; Sen Gupta et al, ).…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…The long timeseries at Leigh Marine Laboratory observes temperature over the annual cycle ranging from 16.5 to 21.0°C (Figure 3). Bowen et al (2017) used an ocean reanalysis to identify the shared impact of atmospheric heat fluxes and oceanic transport of heat in the context of temperature variations at Leigh, whereby the SST Figure 2. Primary river inflows from the New Zealand New Zealand River Environment Classification scheme (Biggs et al 1990) named, with annual flow rates distributed to represent proportional region of freshwater influence (symbolic RoFI) scale, along with example wind roses from New Plymouth, White Island and Nugget Point.…”
Section: Northern Zonementioning
confidence: 99%
“…While this general idea is useful, not all cold water appearing at the ocean surface against a coast is driven by direct winddriven upwelling. Other processes can act to drive this effect also, such as flow-topography interactions, and remote forcing effects such as coastal-trapped waves (Bowen et al 2017). Connectivity -There is a great deal of immediate utility for end-users in developing descriptions of physical transport connectivity (i.e.…”
Section: Yearsmentioning
confidence: 99%